Isolation of furnace oil and crude oil degrading bacteria from soil - Mayaboti, Cinderella Akbar (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.